SPECIAL AND INCLUSIVE MODELS OF EDUCATION IN MODERN AMERICAN AND BRITISH STUDIES - Nataliya Andriichuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article deals with a comparative description of inclusive and special systems of education. On the basis of American and British studies are shown that modern scientists, voluntary organizations and parents of the disabled kids meet two problems: to prove that inclusion is necessary for children with special needs as the alternative to special education and to illustrate the real ways of inclusive education implementation into general educational process. The main goal of inclusive education is defined - to educate an absolutely full member of society by attracting all participants of education process to the general school activities. The author of the article points out that the professionals in the sphere of special education created and worked out a great amount of forms, methods and techniques of teaching which work with particular categories of children with special educational needs. This potential is useful and valuable from the point of view of inclusion which cannot succeed without the professional participation of specialists in different fields of pedagogy, psychology and rehabilitology.